استخدام جهاز الفحص حول السنّي الـ Periotest في تقييم نتائج المعالجة الميكانيكية لالتهابات النسج الداعمة المزمنة - داود, هاشم (Latakia University Journal -Medical Sciences Series, 2019)
هدف البحث إلى دراسة وظيفية لحالة الرباط حول السني باستخدام الـ Periotest في التهابات النسج الداعمة، وتأثير المعالجات حول السنيّة غير الجراحية عليها. شمل البحث اختباراً بالـ Periotest لـ 324 سنّاً لدى 54 مريضاً مصاباً بالتهاب النسج الداعمة، وأخضعوا لمعالجات سنّيّة غير جراحية (تقليح، تسوية جذر)، حيث جرى تقييمهم قبل وبعد ثلاثة أشهر من المعالجة سريرياً بواسطة المُشعرات: عمق السبر PD، المُشعر اللثوي GI، مشعر اللويحة PI، مستوى الارتباط البشري CAL { plaque index (PI), gingival index (GI), probing depth (PD), clinical attachment Loss (CAL)} ووظيفياً بالـ Periotest . وقد أظهرت الدراسة ما يلي: 1) تراجع المقدرة التثبيتية لأربطة الأسنان في التهابات النسج الداعمة، عبّرت عنه قيم مرتفعة للـ Periotest. 2) تُمكّن المعالجة الميكانيكيّة لالتهابات النسج الداعمة المزمنة من تحسين حالة النسج حول السنّيّة سريرياً ووظيفياً (وهذا التحسّن يزداد في المراحل المبكرة للإصابة). 3) إمكانيّة استخدام واسع للـ Periotest في تقييم ومراقبة تغيرات الحالة الوظيفية للرباط حول السنّي وتأثرها بالعوامل الإمراضية المختلفة. 4) الحاجة لمتابعة الدراسات والاختبارات الوظيفية للرباط حول السنّي وتأثير العوامل الإمراضيّة عليه. The purpose of this research is to evaluate the functional and damping characteristics of periodontium, using Periotest and the effect of non-surgical periodontal treatment. The research includes a measurement by periotest for 324 teeth related to 54 patients, suffering from periodontitis treated by non-surgical periodontal treatment (Scaling and root planing). A clinical assessment was made 3 months before and after treatment using plaque index (PI), gingival index (GI), probing depth (PD), clinical attachment loss (CAL) and functional with periotest. The comes up with the following results: 1) A reduction of fixing ability for periodontium ligaments in periodontitis, showed by the high values registered by periotest. 2) Non-surgical mechanical treatment of chronic periodontitis helps improve the periodontal tissues, especially if it is done in the early stages of the diseases. 3) The periotest method enables to evaluate objectively the functional changes for periodontium and the effectiveness pathological factors on it. 4) Further research is necessary to determine the periotest measurements is a valid parameters for assessing the periodontal status of teeth.